Pengaruh Pelatihan Kerja Terhadap Produktivitas Kerja Petugas di Bandar Udara - Aldi Adiatna; Adipura Danang Maulana (Ikatan Da'i Indonesia, 2025)
Job training is a key strategy in human resource management to improve employee quality and productivity, especially in the aviation sector where the work is demanding and service-oriented. Kertajati International Airport, as one of Indonesia's national strategic projects, requires professional, well-trained, and adaptable personnel—particularly in the Aviation Security (AVSEC) unit. However, studies on the effectiveness of training in improving work productivity at airports remain limited. This research uses a quantitative approach with instrument testing (validity and reliability), classical assumption tests, simple linear regression, t-test, and coefficient of determination. The independent variable is job training, while the dependent variable is the work productivity of AVSEC personnel at Kertajati Airport. Data were collected through questionnaires distributed to personnel who had undergone training. The results show that job training has a positive and significant effect on work productivity. Training improves discipline, technical skills, and work motivation. The coefficient of determination of 31.1% indicates that training contributes significantly to productivity, although other factors such as motivation and work environment also play important roles in supporting overall performance.